Assessment of damage caused by Athaumastus haematicus (Stål, 1860) (Hemiptera: Coreidae) in sunflower, Helianthus annuus (L.) (FAVE Sección Ciencias Agrarias, 2025)
Athaumastus haematicus (Hemiptera: Coreidae), commonly known as the "bloodsucking bug," "red bug," or "bean bug," is frequently found in sunflower (Helianthus annuus) crops. Currently, there is no quantification of its impact on yield nor a characterization of the genotypic susceptibility of commercial hybrids. The objectives of this study were (i) to assess the incidence and severity of the typical symptoms caused by A. haematicus in commercial sunflower hybrids and (ii) to quantify the yield loss per plant due to A. haematicus infestation. A rating scale was developed to evaluate incidence and severity in 38 commercial sunflower hybrids, and the effect of A. haematicus on yield, oil content, and numerical yield components was analyzed in two field trials conducted in the central region of Santa Fe province, Argentina. The results revealed a group of hybrids with lower levels of incidence and severity, as well as a significant yield loss per plant directly attributable to A. haematicus. This is the first study to quantify both the impact of this pest on yield and the tolerance of certain sunflower genotypes. Future research should focus on establishing economic injury thresholds, continuing the evaluation of hybrid sensitivity, investigating the genotypic mechanisms underlying the observed tolerance, and determining effective active ingredients for pest management.
Keywords: red bug, coreid bug damage, genotype susceptibility, yield loss